2023
DOI: 10.3390/nu15153453
|View full text |Cite
|
Sign up to set email alerts
|

WISER Survivor Trial: Combined Effect of Exercise and Weight Loss Interventions on Adiponectin and Leptin Levels in Breast Cancer Survivors with Overweight or Obesity

Abstract: Adipocyte dysregulation is one mechanism linking overweight and breast cancer recurrence. Exercise and weight loss are associated with a decreased risk of breast cancer recurrence in breast cancer survivors with overweight or obesity, which may be mediated through reduced leptin levels, increased adiponectin levels, and an elevated adiponectin to leptin (A:L) ratio. The four-arm randomized controlled WISER Survivor trial examined the 12-month intervention effects of exercise, weight loss, and the combination o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
0
1
0
Order By: Relevance
“…Goodwin and colleagues [ 21 ] reported similar relative changes with metformin compared to placebo in their MA.32 trial, despite lower baseline leptin levels, in line with the lower median BMI in their trial. The WISER Survivor trial in overweight/obese breast cancer survivors observed significant decrements in leptin in the weight loss arms [ 22 ]. Adiponectin favorably increased only in the lifestyle intervention group.…”
Section: Discussionmentioning
confidence: 99%
“…Goodwin and colleagues [ 21 ] reported similar relative changes with metformin compared to placebo in their MA.32 trial, despite lower baseline leptin levels, in line with the lower median BMI in their trial. The WISER Survivor trial in overweight/obese breast cancer survivors observed significant decrements in leptin in the weight loss arms [ 22 ]. Adiponectin favorably increased only in the lifestyle intervention group.…”
Section: Discussionmentioning
confidence: 99%
“…Exercise could be an easy and effective approach to stimulate the secretion of adiponectin, BDNF, and GLP-1 in both nonobese and obese individuals. Several studies have shown that consistent exercise can increase the levels of adiponectin [ 51 ], BDNF [ 52 ], and GLP-1 [ 53 ] in the blood of both nonobese and obese people.…”
Section: Discussionmentioning
confidence: 99%